Pengelolaan Dana BOS BOMM di Madrasah (Studi tentang Efektifitas Pengelolaan Dana BOS dan BOMM di MI dan MTs) - Nurhattati Fuad (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
One of the governmental policies for the madrasah quality improvement is providing programs called biaya operasional sekolah (BOS) and bantuan operasional manajemen mutu (BOMM). Both programs, basically, aim at improving the quality of education in madrasah at the basic education level (Madrasah ibtidaiyah and madrasah tsanawiyah). This study wants to describe how those programs be implemented. In a detail, the survey focuses on: (1) mechanism in carrying out program of BOS and BOMM, including how its socialization, distribution, utilization, and its accountability, (2) the effect of both programs towards the quality improvement of madrasahs, and (3)advisory treatments carried out by the government dealing with the implementation of BOSS and BOMM programs. The study highlights that the BOS and BOMM programs have contribute in improving the madrasahs performance which, in turn, help the quality improvement of madrasahs. Finally, the research recommended to the government to continue these programs in the future with any notes to be refined.